ESTIMATION OF STANDARD-STATE ENTROPIES OF ASSOCIATION FOR AQUEOUS METAL-ORGANIC COMPLEXES AND CHELATES AT 25°C AND 1 BAR - Prapaipong P.; Shock E.L. (My University, 2001)
Linear correlations between entropies of association for metal-organic complexes and chelates (ΔSr) and standard partial molal entropies of aqueous cations (SM) at 25°C and 1 bar are identified to estimate the temperature dependence for association constants of aqueous metal-organic complexes and chelates. The correlations are systematically dependent on ligand structure and cation coordination number as revealed by common slopes of -0.15, -0.32, -0.84, and -0.92 for complexes of monocarboxylate ligands, dicarboxylate ligands, and ligands consisting of three and four carboxyl groups, respectively. The grouping of different types of ligands allows the use of structural considerations in the correlation methods, which provide rapid estimation of the temperature dependence of association constants. These developments expand the number and variety of metal-organic complexes and chelates that can be included in theoretical models of the distribution, transport, and bioavailability of metals in geochemical and environmental processes.